TINDAK TUTUR TOKOH DALAM NOVEL SI ANAK BADAI KARYA TERE LIYE - Devi, Mutia Sari (Hasta Wiyata, 2024)
The purpose of this study is to describe how the illocutionary acts and locutionary acts in the novel Si Anak Badai Karya Tere Liye. This type of research is qualitative descriptive. Data collection techniques in this study with the library and data collection tools of this study as a key instrument. Researchers found 390 locus speech acts and illocutionary speech acts. It seems important in novel Si Anak Badai Karya Tere Liye that the characters prefer speech acts because they talk more about what is said. Likewise, the illocutionary acts in the novel Si Anak Badai Karya Tere Liye, the characters take over the activities. With this it can be concluded that there are locus and illocutionary acts in the novel Si Anak Badai Karya Tere Liye